The Role of Corporate Value in Mediating Inflation and BI Rate on Indonesia's Sharia Stock Prices - Suhendi, Suhendi; Rusiadi, Rusiadi; Safrida, Winda; Nasution, Lia Nazliana; Rangkuty, Dewi Mahrani (Atestasi : Jurnal Ilmiah Akuntansi, 2023)
Economic development and expansion are the driving forces behind this research, and one way to achieve these goals is through participating in the capital market by purchasing and selling shares. The purpose of this study is to identify the following variables as confounding factors: company value, inflation, and the bi-ratio of sharia stock prices. This study makes use of historical data, with 17 companies that are listed on the BEI-Mes serving as the population. Multiple linear regression analysis and route analysis are used in data analysis. The findings of the partial test data analysis (t test) indicate that firm value has a positive and significant impact on sharia share prices, while bi rate has a negative but not statistically significant impact. Inflation also has a partial positive impact on sharia stock prices. Whereas inflation has a huge and negative impact on firm value, the bi rate has a positive and considerable impact on it. Furthermore, path analysis findings indicate that the bi rate and inflation have a major impact on the price of sharia stocks, with company value acting as a mediating factor